PERANCANGAN PERANGKAT LUNAK PENJADWALAN MATA KULIAH DI FAKULTAS TEKNIK UNIVERSITAS TRUNOJOYO MADURA - Vivi Tri Widyaningrum; Sri Wahyuni (Jurnal Teknologi Informasi dan Terapan, 2019)
Scheduling of the courses is a very complex problem and requires precision, and should be based on rules (constraints) scheduling applies to generate an optimal schedule. UTM's Faculty of Engineering is currently in charge of six courses and the even semester FY 2014 -2015 has begun implementing a centralized scheduling system in a faculty that is directly under the direction of Assistant Dean I. In a centralized scheduling system was introduced lecturers sharing, which means that a professor can teach in several different study programs. This leads to the possibility of conflicting lecture schedules so great that in this scheduling need to be checked on a schedule of all courses of study in order to schedule formed in accordance with the rules (constraints) applies. Currently the process of scheduling at the Faculty of Engineering UTM still usin g traditional methods, namely the preparation of manually so that the design of the scheduling of courses with the method of simulated annealing (SA) this needs to be made, in order to begin to be made centralized scheduling can be made more optimal. In addition, the scheduling will be more easily modified if there are changes to the schedule of lectures.